Biofield Energy – History and Applications of Kinesiology Muscle Testing - Bhattessa, Seema (British Journal of Healthcare and Medical Research, 2024)
In the 1960s, a chiropractor in the United States adapted manual muscle testing (MMT), a procedure in which muscle strength and nerve function are subjectively assessed, as a method for evaluating and correcting structural imbalances, naming the practice Applied Kinesiology (AK). The practice of AK was eventually developed into a multifaceted system using MMT as a means through which information about the function of organs and systems can be derived. AK cites the neurological principle of sensory and motor integration known as the central integrated state, i.e., the summative effects of all activating and inhibiting influences on motor output, as the basis for the ability of MMT to reflect organ function beyond that of muscle or nerve function alone. Over the ensuing decades, interest in this evaluative technique has expanded beyond the chiropractic profession, and it has been adapted for use in a number of both conventional and complementary healthcare disciplines. This review article briefly explores the history and applications of MMT as an evaluative tool.